1990
DOI: 10.1002/mar.4220070404
|View full text |Cite
|
Sign up to set email alerts
|

Children's use of perceptual cues in product categorization

Abstract: This study examines how young children use perceptual cues in categorizing products. Specifically, we examine the notion that young children use perceptual cues in a more informed fashion than is generally assumed by traditional viewpoints on cognitive development. Data from the three age groups—four‐ and five‐year‐olds, six‐ and seven‐year‐olds, and adults—confirm that even young children can use perceptual cues in a manner that is diagnostic of product category membership and that this ability increases with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Moreover, the results from Studies 1, 2, and 3 support our hypothesis: Children generated a higher proportion of perceptual cues than young adults, for all inference tasks. These findings fit with the definition of children as ‘perceptually oriented’ (Flavell, ; John & Sujan, ; Wartella, Daniel, Scott, Jacob, & Allison, ). Younger children have overall less knowledge of and experience with objects and their hidden features and tend to spontaneously focus on perceptual over hidden properties (Gelman & Davidson, ; Gentner, ; Keil & Batterman, ).…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, the results from Studies 1, 2, and 3 support our hypothesis: Children generated a higher proportion of perceptual cues than young adults, for all inference tasks. These findings fit with the definition of children as ‘perceptually oriented’ (Flavell, ; John & Sujan, ; Wartella, Daniel, Scott, Jacob, & Allison, ). Younger children have overall less knowledge of and experience with objects and their hidden features and tend to spontaneously focus on perceptual over hidden properties (Gelman & Davidson, ; Gentner, ; Keil & Batterman, ).…”
Section: Discussionsupporting
confidence: 83%
“…Because we employed a task and instructions that encouraged thematic processing, we expected, based on the results of previous research (e.g., John and Sujan 1990), that animate objects, since they are thought to enhance thematic categorization (Blanchet, Dunham and Dunham 2001), would be more accurately categorized. The nature of our task encouraged thematic processing because we allowed the children to make direct comparisons (as in Namy 1999 andGentner 2002) between the objects and each environment, and we used object labels (as in Gelman and Markman 1987).…”
Section: Resultsmentioning
confidence: 99%
“…Butter et al (1991), for instance, found that OTC medicine commercials do not, in general, influence children's choices concerning use of those medicines. However, John and Sujan (1990) found that even young children can use perceptual cues in a manner that is diagnostic of product category membership and, further, that this ability increases with age. Macklin (1990) found that casting older models was better for products aimed at young children, but this varied for product types and could be influenced by product motivation.…”
Section: Factors Affecting Information Processing Attitudes and Choicementioning
confidence: 93%
“…Yi and Gray (1996) introduced an application of "attribute diagnosticity" as an "attribute's usefulness for distinguishing instances from non-instances of a category" (p. 605) and as a key determinant of an ambiguous product's typicality as a member of a category. John and Sujan (1990) found that young children can use perceptual cues in a manner that is diagnostic of product category membership and that this ability increases with age. Consistent with Jacoby, Johar, and Morrin's (1998) observation that metaphor applications, as a growing body of categorization research, are also evident in P&M, Ji (2002), for instance, used metaphors such as first love, arranged marriage, one-night stand, good friend, buddy, and enmity to categorize child-brand relationships.…”
Section: Attentionmentioning
confidence: 97%